Cleaning and disinfection programs against Campylobacter jejuni for broiler chickens: Productive performance, microbiological assessment and characterization - De Castro Burbarelli, Maria Fernanda (2018)
Detailed cleaning and disinfection programs aims to reduce infection pressure from microorganisms from one flock to the next. However, studies evaluating the benefits to poultry performance, the sanitary status of the facilities, and the sanitary quality of the meat are rarely found. Thus, this study was designed to evaluate 2 cleaning and disinfecting programs regarding their influence on productive performance, elimination of Campylobacter, and characterization of Campylobacter jejuni strains when applied to broiler chickens’ facilities. Two subsequent flocks with 960 birds each were distributed into 32 pens containing 30 birds each. In the first, the whole flock was inoculated with a known strain of Campylobacter jejuni in order to contaminate the environment. In the second flock, performance and microbiological evaluations were done, characterizing an observational study between 2 cleaning and disinfection programs, regular and proposed. The regular program consisted of sweeping facilities, washing equipment and environment with water and neutral detergent. The proposed cleaning program consisted of dry and wet cleaning, application of 2 detergents (one acid and one basic) and 2 disinfectants (250 g/L glutaraldehyde and 185 g/L formaldehyde at 0.5% and 210 g/L para-chloro-meta-cresol at 4%). Total microorganism count in the environment and Campylobacter spp. identification were done for the microbiological assessment of the environment and carcasses. The positive samples were submitted to molecular identification of Campylobacter spp. and posterior genetic sequencing of the species identified as Campylobacter jejuni. The birds housed in the facilities and submitted to the proposed treatment had better performance when compared to the ones in the regular treatment, most likely because there was a smaller total microorganism count on the floor, walls, feeders and drinkers. The proposed program also resulted in a reduction of Campylobacter spp. on floors, drinkers and birds. Moreover, it was possible to identify 6 different Campylobacter jejuni strains in the facilities. The proposed treatment resulted in a positive influence on the birds’ performance and reduction of environment contamination for broiler chickens.